2018
DOI: 10.1016/j.semcancer.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in ovarian cancer

Abstract: Ovarian cancer is a disease with a poor prognosis and little progress has been made to improve treatment. It is now recognized that there are several histotypes of ovarian cancer, each with distinct epidemiologic and genomic characteristics. Cancer therapy is moving beyond classical chemotherapy to include epigenetic approaches. Epigenetics is the dynamic regulation of gene expression by DNA methylation and histone post translational modification in response to environmental cues. Improvement in technology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 134 publications
(142 reference statements)
3
96
0
2
Order By: Relevance
“…The genetic changes in OC results from chromosome instability (CIN) [7,36]. High levels of CIN have been reported in HGSOC [37]. CIN may result from the stimulus arising from the peritoneal microenvironment.…”
Section: Genetic Changesmentioning
confidence: 99%
“…The genetic changes in OC results from chromosome instability (CIN) [7,36]. High levels of CIN have been reported in HGSOC [37]. CIN may result from the stimulus arising from the peritoneal microenvironment.…”
Section: Genetic Changesmentioning
confidence: 99%
“…Mounting evidence reveals that ovarian carcinogenesis is an interplay among genetics, epigenetics and transcriptomics. Strikingly, epigenetic regulation may change gene expression to facilitate ovarian cancer development 4‐6 . RNA methylation is one form of epigenetic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation, the most studied epigenetic mechanism, is reported to be related to mRNA and miRNA expression regulation, thus contribute to cancer initiation or progression [7]. Recently, more and more studies indicated that abnormal gene methylation in promoter regions is involved with chemical therapy and targeting therapy of ovarian cancer [8][9][10].…”
Section: Introductionmentioning
confidence: 99%